Копье Милосердия: роман / В. Д. Гладкий - Гладкий Виталий Дмитриевич (Русский авантюрный роман, 2011)
Экземпляры: аб. (2012) / Инвентарный номер: 54113 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Г 52 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44